SOSIS “LEBOYA” IKAN LELE DUMBO DAN TEPUNG KACANG KEDELAI ALTERNATIF MAKANAN SELINGAN SUMBER PROTEIN DENGAN GLUTEN FREE CASEIN FREE UNTUK ANAK AUTISM SPECTRUM DISORDER - Indriani, Wini; Isdiany, Nitta; Gumilar, Mulus; Priawantiputri, Witri (Jurnal Gizi dan Dietetik, 2024)
The World Health Organization (WHO) reports that approximately one in 160 children worldwide has Autism Spectrum Disorder. (ASD) According to a 2016 report from the Centers for Disease Control and Prevention, about 1 in 54 children in the United States is diagnosed with an autism spectrum disorder. The Central Bureau of Statistics currently in Indonesia there are around 270.2 million with a growth ratio of autistic children around 3.2 million children. One of the interventions provided is dietary therapy with gluten and casein free. Giving children with autism foods that contain gluten and casein will be one of the triggers for the emergence of aggressive attitudes in the brain. One alternative to gluten-free and casein-free protein sources is Leboya Sausage, which is dumbo catfish sausage with soybean flour that can be made independently or in groups by utilizing food ingredients that are easy to find and can be used as a source of protein for children with Autism Spectrum Disorder. The purpose of this study was to determine the effect of dumbo catfish formulation with soy bean flour on organoleptic properties, energy, protein, fat and carbohydrate content and price of leboya sausage. This research design is experimental and the sample in organoleptic testing is 30 moderately trained panelists. The results of the study on the organoleptic properties of the three formulas showed significant differences with p (0.005) < α (0.05) in texture, significant differences with (0.038) < α (0.05) in overall and no significant differences in taste, aroma and color with p > 0.05. F1 is the best formula that panelist likes. The results of the proximate test obtained nutritional values/100 grams, namely ash content 2.2%, energy from fat 82.8 kcal, total fat content 9.2, water content 60.1%, total energy 196.7 kcal, carbohydrates 18.14 grams and protein 10.32 grams with a unit price of serving (60 grams) which is Rp. 2,292. . Key words: Autism Spectrum Disorder, Dumbo Catfish, Soy Bean Flour.